2013
DOI: 10.4271/2013-01-0921
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of an IC Engine Turbocharger in Critical Conditions of Lubrication

Abstract: Problems in the turbocharger lubrication system can cause serious deterioration in their overall performance and even their complete destruction. The paper describes several tests with different critical lubrication conditions, in order to determine the thresholds at which the operation may be appropriate. In an IC engine, these problems can be produced mainly by several factors: the decreasing in the supply pressure of the oil, a delay in the lubrication oil pressure and an intermittent lubrication interrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The study covered TCR critical operating conditions: with insufficient oil pressure, delayed oil supply, and the periodic interruption of lubrication. The results showed that during acceleration and especially at high acceleration rates, significant malfunctions of and damage to the TCR appeared [17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study covered TCR critical operating conditions: with insufficient oil pressure, delayed oil supply, and the periodic interruption of lubrication. The results showed that during acceleration and especially at high acceleration rates, significant malfunctions of and damage to the TCR appeared [17].…”
Section: Introductionmentioning
confidence: 98%
“…The behavior of the lubricant flow in the plain bearings of the TCR shaft was studied in [15,16,17]. Chuepeng et al [15] found that high oil inlet temperatures contribute to high TCR efficiency, while oil viscosity does not significantly affect the turbine pressure or the operation ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Serrano et al [8] study the robustness of several turbochargers ingestion of different elements such as screws, sand or water with the compressor. Galindo et al [9] also study the mechanical behaviour of turbochargers with intermittent stops of the lubricating oil flow. In the literature, several studies about turbocharger endurance and loss of efficiency have been found.…”
Section: Introductionmentioning
confidence: 99%
“…An automotive turbocharger shaft can easily achieve rotational speeds higher than 200 krpm, and floating or semifloating journal bearings are usually used. Galindo et al [13] also study the mechanical behaviour of turbochargers with intermittent stops of the lubricating oil flow. The temporal lack of lubrication leads to wear of the bearings and final imbalance of the shaft very quickly.…”
Section: Introductionmentioning
confidence: 99%